Changes in caregiver burden and health‐related quality of life of informal caregivers of older people with Dementia: evidence from the European RightTimePlaceCare prospective cohort study. (17th November 2014) - Bleijlevens, Michel H.C.; Stolt, Minna; Stephan, Astrid; Zabalegui, Adelaida; Saks, Kai; Sutcliffe, Caroline; Lethin, Connie; Soto, Maria E.; Zwakhalen, Sandra M.G.; the RightTimePlaceCare Consortium
Abstract Aims To describe differences in caregiver burden and health‐related quality of life of informal caregivers of people with dementia in eight European countries and assess changes after transition from home to institutional long‐term care. Background Country differences in the experience of burden and health‐related quality of life are rarely described. Design Prospective cohort study. Methods Data on burden and health‐related quality of life were collected at baseline (conducted between November 2010–April 2012) and follow‐up (after 3 months) using face‐to‐face interviews. Two groups of informal caregivers included those: (1) of people with dementia recently admitted to institutional long‐term care facilities; and those (2) of people with dementia receiving home care. Statistical analyses focused on descriptive comparisons between groups and countries. Results Informal caregivers of about 2014 were interviewed. Informal caregivers of people with dementia at home experienced more burden compared with informal caregivers of recently institutionalised people with dementia. Almost no differences in health‐related quality of life were found between groups. Large differences between countries on outcomes were found. Informal caregivers of people with dementia who made the transition to an institutional long‐term care facility experienced a statistically significant decrease in burden and psychological distress at follow‐up. Conclusion Cross‐country differences may be related to differences in health and social care systems. Taking this into account, informal caregiver interventions need to be tailored to (country specific) contexts and (individual) needs. Findings highlight the positive impact of admission to institutional long‐term care on informal caregiver well‐being.